2014
DOI: 10.1007/s00467-014-3002-5
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal glomerular filtration rate in children, adolescents and young adults starts below 75 mL/min/1.73 m2

Abstract: Background The chronic kidney disease (CKD) classification system for children is similar to that for adults, with both mainly based on estimated glomerular filtration rate (eGFR) combined with fixed cut-off values. The main cut-off eGFR value used to define CKD is 60 mL/min/1.73 m 2 , a value that is also applied for children older than 2 years of age, adolescents and young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 35 publications
(32 reference statements)
4
49
0
1
Order By: Relevance
“…Stage 3 CKD (creatinine clearance o60 ml/min/1.73 m 2 ) is defined as chronic renal insufficiency; it has been suggested that in children and adolescents a clearance below 75 ml/min/1.73 m 2 is a sign of active disease that requires further assessment [9]. Stage 5 is also known as ESRD, where renal replacement therapy is required, i.e., dialysis or renal transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Stage 3 CKD (creatinine clearance o60 ml/min/1.73 m 2 ) is defined as chronic renal insufficiency; it has been suggested that in children and adolescents a clearance below 75 ml/min/1.73 m 2 is a sign of active disease that requires further assessment [9]. Stage 5 is also known as ESRD, where renal replacement therapy is required, i.e., dialysis or renal transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric patients (age <18 years) about to start on MTX or platinumbased antineoplastic therapy in the Hospital do Cancer Infantil in Fortaleza, Ceará, Brazil, were eligible for entry into the study. To avoid any bias in urinary KIM-1 measurements, those patients with reduced baseline renal function [estimated glomerular filtration rate (eGFR)<75 mL/ min/1.73 m 2 ] [17] were not included. Also, patients were excluded if they had a known diagnosis of chronic kidney disease, including dialysis or transplantation, a previous history of renal disease, or if they had received any other known nephrotoxic drug in the previous 30 days.…”
Section: Subjectsmentioning
confidence: 99%
“…The presence of obesity or overweight was not considered an exclusion criterion. The following tests were additionally obtained from the subjects in the hypertensive group: microalbuminuria (abnormal values between 30 to 300 mg/g creatinine), 16 glomerular filtration rate (GFR; abnormal values below 75 mL/min/1.73 m²), 17 and basal insulin (normal values between 5 and 25 µU/mL). 6 The adolescents were divided into three groups: group I (GI; n = 108, 58 males, mean age 15.2 ± 2.2 years), comprising healthy, nonhypertensive adolescents born to healthy parents without a diagnosis of or taking any medication for hypertension, dyslipidemia, or diabetes; group II (GII; n = 53, 28 males, mean age 13.9 ± 1.4 years), comprising adolescents with confirmed hypertension; and group III (GIII; n = 74, 31 males, mean age 14.9 ± 2.2 years), comprising healthy, nonhypertensive adolescents whose parents a) were being treated for dyslipidemia or presented baseline levels of TC ≥ 200 mg/dL, LDL-C > 130 mg/dL, HDL-C < 40 mg/dL, or TG ≥ 150 mg/dL; b) had diabetes mellitus or a fasting plasma glucose ≥ 100 mg/dL; and c) were taking medications for hypertension or presented a systolic BP ≥ 140 mmHg or diastolic BP ≥ 90 mmHg.…”
Section: -14mentioning
confidence: 99%